Strategies for Prevention, Protection, and Repair of Bridge Girders Vulnerable to Over-height Vehicle Impacts: A State-of-the-Art Review. (October 2022) - Das, Shagata; Brenkus, Natassia R.; Tatar, Jovan
Abstract: Damage of highway bridges due to over-height vehicle collisions is experiencing a noteworthy increase in the United States. This paper provides an overview of various prevention and protection schemes, including re-routing methods, warning systems, clearance augmentation, impact absorbers, and a description of contemporary damage repair techniques. This review of the state-of-the-art will assist practitioners in their selection of appropriate damage mitigation methods, categorization of typical damage, and selection of appropriate repair techniques. Further research in full-scale over-height vehicle-bridge impact would advance characterization of the collision mechanism, facilitating the development of appropriate impact protection systems and damage repair guidelines.